Predictors of Cord Blood Leptin Level in Pregnancies Complicated With Preeclampsia, Fetal Growth Restriction and in Normal Pregnancies - Nilgün Öztürk Doğan; Serdar Yalvaç; Eray Çalışkan; Asuman Erten; İsmail Dölen; Ali Haberal (Medical Network, 2007)
OBJECTIVE: To investigate possible predictors of cord blood leptin level in pregnancies complicated with fetal growth restriction, preeclampsia and in normal pregnancies. STUDY DESIGN: Thirty-two pregnant women with intrauterine growth restriction (IUGR), 28 women with preeclampsia and randomly selected 36 normal pregnant women were enrolled. Umbilical cord blood samples were collected for measurements of leptin, cortisol and blood gas after delivery. RESULTS: Cord blood leptin level was significantly lower in the IUGR group (8.9±9ng/ml, p=0.01) compared to control group (18.8±15.8) but not different from preeclampsia group (14.8±15.8). Cord blood cortisol level was significantly higher in the preeclampsia group (27.8±13.4 Ug/dl, p=0.005) compared to control group (19.5±9.2) and IUGR group (18.6±12.7). Multiple lineer regression model revealed that fetal birth weight, fetal gender, gestational age, maternal hematocrite, cord blood cortisol level, cord blood hematocrite and presence of fetal intrauterine growth restriction were all independent predictors of cord blood leptin level. CONCLUSION: Regulation of cord blood leptin level is a complex process involving fetal gender and fetal anthropometric variables as well as cord blood cortisol, intrauterine growth and hypoxia. Leptin level is decreased in cases of placental insufficiency like IUGR but not in uncomplicated preeclampsia alone.